First geo-marine survey of living cold-water Lophelia reefs in the Ionian Sea (Mediterranean basin) - TAVIANI M.; REMIA A.; CORSELLI C.; FREIWALD A.; MALINVERNO E.; SAVINI A.; MASTROTOTARO, FRANCESCO; TURSI, Angelo Raffaele (2005)
Prosperous deep coral mounds including living colonies of Lophelia pertusa together with Madrepora oculata and Desmophyllum dianthus (= D. cristagalli) have been discovered in 2000, by fishery operations on the eastern side of the Ionian Sea. The living coral mounds are located between ca. 300 and 1,100 m on a gently dipping shelf off Apulia at Santa Maria di Leuca (SML), and characterized by a complex seabed topography. Side scan sonar, shallow high-resolution seismics and sampling indicate that these Lophelia-bearing coral mounds colonize quasi-indurate (firmground) Pleistocene sediment. At places live corals were found on Pleistocene coral-hardgrounds. The fauna associated with these Ionian modern coral mounds is less diversified than modern Eastern Atlantic counterparts. The core of living coral mounds colonies is at present located in 500–700 m and is tentatively suggested that their survival is mostly controlled by oceanographic factors. The SML coral banks represent so far a unique example of living Lopheliabearing coral mounds in the Mediterranean basin.